Analisis Bibliometrik atas Publikasi Ilmiah di Indonesia: Refleksi Kritis 2020–2025 - Wekke, Ismail Suardi; Ismail, Rudihartono; Adi, Tiomy Butsianto (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
Bibliometric research in Indonesia has experienced significant developments in the period 2020–2025, along with increasing attention to the quantification of scientific literature and mapping of research trends. This study aims to provide a comprehensive overview of the growth of bibliometric research in Indonesia, identify the most productive researchers and institutions, and evaluate its implications for the national research ecosystem. By analyzing data from Scopus and Google Scholar, an exponential increase in the number of publications with the keywords “bibliometric” and “Indonesia” was found. Leading universities such as the University of Indonesia, Universitas Gadjah Mada, and Universitas Airlangga are the main contributors. The implications of this trend include increased methodological awareness, multidisciplinary collaboration, and the potential for integrating bibliometrics into national research policies. This study provides a basis for researchers and policymakers to understand the direction and quality of scientific research in Indonesia.